Three Years Journal of IJSTM (International Journal of Science Technology & Management: Inarah): A Bibliometric Analysis - Hidayat, M.Syamsul; Budi Utami (Publisher Cv. Inara, 2022)
International Journal of Science ,Technology & Management (IJSTM: Inarah) is an internationally reputed journal with a Copernicus index that publishes original, peer-reviewed, and empirical research in science, technology and management. The use of technology in real business activities is often found in IJSTM journal articles. This journal has reached its 3rd year of publication in 2019. Using bibliometric techniques, we analyze based on the journal's authors, salient topics, and the most prolific authors, including institutions and affiliated countries as well as .topic relationships between articles. In network analysis using VOSviewer software, the results of IJSTM publications based on the linkage of articles are that there are two clusters, Keywords: IJSTM Journal, Bibliometrics, Vos Viewer